Examination of How and Why Over-the-Bed Tables Are Used: Use Cases and Needs from Healthcare Providers. (January 2014) - Manganelli, Joe; Threatt, Anthony; Brooks, Johnell O.; Healy, Stan; Merino, Jessica; Yanik, Paul; Walker, Ian; Green, Keith
OBJECTIVE: This article presents the results of an exploratory study in which 14 clinical and staff subject matter experts (SMEs) at a regional rehabilitation hospital were interviewed in order to understand how and why over-the-bed tables are used. BACKGROUND: It is important to understand how and why a device or environment is used when designing it, and not just what features and functions are preferred. This knowledge is valuable both for contextualizing user feature and function preferences and for characterizing and prioritizing design challenges and opportunities. METHODS: Fourteen hospital clinical and support staff subject-matter experts participated in semi-structured interviews with scenario enactments in a medium-fidelity, full-scale mock-up of a typical patient room. During these interviews, they interacted with two personas played by actors and were asked to enact an example of a normal visit, from entering the room through treatment/service and then exiting. Data were analyzed via methodological triangulation including frequency analysis, content analysis, and affinity diagramming. RESULTS: The results include a use-case analysis with illustrative sketches, a list of needs statements, and final observations. CONCLUSIONS: Successfully using the over-the-bed table is dependent upon proper positioning, especially in bed during meals. There are fewer problems associated with over-the-bed table use while seated in a chair than when in the bed. The over-the-bed table is a key component in acute care, inpatient therapies. Clinicians are generally open to "smart" furniture in the patient room but question its cost-effectiveness, robustness, and flexibility.